Cobertura glaciar de los nevados del distrito de Catac, Ancash y su relación con la precipitación y temperatura durante el periodo 1988-2022 - Chuquilin-Goicochea, Roberto; Palacios-Miñano, Alberto; Domínguez-Marchena, Rosnell (LACCEI, 2024)
The objective of this research was to analyze how precipitation and temperature affect changes in the glacial coverage of the snow-capped mountains of the Catac district during the period from 1988 to 2022. An applied study was carried out with an explanatory level and a longitudinal design. non-experimental, since the period from 1988 to 2022 was temporally analyzed. The remote sensing technique and the NDSI index (Normalized Differential Snow Index) were used to recognize the glacier, and the climate information was obtained from the PISCO-SENAMHI grid product. A decrease in glacier coverage was observed at a rate of 0.73 km2 per year. The statistical correlation analysis revealed that temperature is the only factor that significantly influences changes in glacier cover, while precipitation is part of the glaciological balance system, but its influence on surface changes is not significant due to a superficial and non-volumetric analysis. In conclusion, the increase in temperature has a notable impact on glacier coverage, through the melting and instability of the ice.